Antimicrobial Resistance Profiles, Virulence Genes, and Genetic Diversity of Thermophilic Campylobacter Species Isolated From a Layer Poultry Farm in Korea - Gahamanyi, Noel; Song, Dae-Geun; Yoon, Kye-Yoon; Mboera, Leonard E. G.; Matee, Mecky I.; Mutangana, Dieudonné; Amachawadi, Raghavendra G.; Komba, Erick V. G.; Pan, Cheol-Ho (Frontiers in Microbiology, 2021)
Thermophilic Campylobacter species are among the major etiologies of bacterial enteritis globally. This study aimed at assessing the antimicrobial resistance (AMR) profiles, virulence genes, and genetic diversity of thermophilic Campylobacter species isolated from a layer poultry farm in South Korea. One hundred fifty-three chicken faeces were collected from two layer poultry farms in Gangneung, South Korea. Campylobacter species were isolated by cultural techniques while PCR and sequencing were used for species confirmation. Antimicrobial susceptibility testing for six antimicrobials (ciprofloxacin (CIP), nalidixic acid (NAL), sitafloxacin (SIT), erythromycin (ERY), tetracycline (TET), and gentamicin (GEN)) was carried out by broth microdilution. Three AMR and nine virulence genes were screened by PCR. Genotyping was performed by flaA-RFLP and multilocus sequence typing (MLST). Of the 153 samples, Campylobacter spp. were detected in 55 (35.9%) with C. jejuni and C. coli being 49 (89.1%) and 6 (10.9%), respectively. High-level resistance was observed for CIP (100%), NAL (100%) and TET (C. jejuni: 93.9%; C. coli: 83.3%). No resistance was observed for SIT. The missense mutation (C257T) in gyrA gene was confirmed by sequencing while the tet(O) gene was similar to known sequences in GenBank. The rate of multidrug-resistant (MDR) strains was 8.2% and all belonged to C. jejuni. All Campylobacter isolates possessed five virulence genes (cdtB, cstII, and flaA, cadF, and dnaJ) but none possessed ggt while rates for other genes (csrA, ciaB, and pldA) ranged between 33.3 and 95.9%. The flaA-RFLP yielded 26 flaA types (C. jejuni: 21 and C. coli: 5) while the MLST showed 10 sequence types (STs) for C. jejuni and 3 STs for C. coli with CC-607 (STs 3611) and CC-460 (ST-460) being predominant. Among the 10 STs of C. jejuni, three were newly assigned. The findings of this study highlight the increased resistance to quinolones and tetracycline, the virulence potential, and diverse genotypes among Campylobacter strains isolated from the layer poultry farm.